Biotransformation of Lignin by an Artificial Heme Enzyme Designed in Myoglobin With a Covalently Linked Heme Group - Guo, Wen-Jie; Xu, Jia-Kun; Liu, Jing-Jing; Lang, Jia-Jia; Gao, Shu-Qin; Wen, Ge-Bo; Lin, Ying-Wu (Frontiers in Bioengineering and Biotechnology, 2021)
The conversion of Kraft lignin in plant biomass into renewable chemicals, aiming at harvesting aromatic compounds, is a challenge process in biorefinery. Comparing to the traditional chemical methods, enzymatic catalysis provides a gentle way for the degradation of lignin. Alternative to natural enzymes, artificial enzymes have been received much attention for potential applications. We herein achieved the biodegradation of Kraft lignin using an artificial peroxidase rationally designed in myoglobin (Mb), F43Y/T67R Mb, with a covalently linked heme cofactor. The artificial enzyme of F43Y/T67R Mb has improved catalytic efficiencies at mild acidic pH for phenolic and aromatic amine substrates, including Kraft lignin and the model lignin dimer guaiacylglycerol-β-guaiacyl ether (GGE). We proposed a possible catalytic mechanism for the biotransformation of lignin catalyzed by the enzyme, based on the results of kinetic UV-Vis studies and UPLC-ESI-MS analysis, as well as molecular modeling studies. With the advantages of F43Y/T67R Mb, such as the high-yield by overexpression in E. coli cells and the enhanced protein stability, this study suggests that the artificial enzyme has potential applications in the biodegradation of lignin to provide sustainable bioresource.